Enhancement of CO2 uptake in iso-reticular Co based zeolitic imidazolate frameworks via metal replacement - Panda, Tamas; Gupta, Krishna M.; Jiang, Jianwen; Banerjee, Rahul (CrystEngComm, 2014)
Three Co based Zeolitic Imidazolate Frameworks (Co-ZIF-68, -69 and -81) which adopt a GME topology with high porosity have been synthesized. These Co-ZIFs show high CO2 (273 K/298 K) uptake compared to their isostructural Zn based analogues, which has been proved experimentally as well as by ab initio calculations.